Developing English writing instructional materials for second year university students of English Department - Phalychan, Bounmy; Sugirin, Sugirin (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2019)
This research was aimed at developing English writing instructional materials that are appropriate for second-year students of English Department at Champasak University. This research was a Research and Development study using model proposed by Jolly and Bolitho (1998). The subjects of this research were 30 learners who are students of English Department at Champasak University. Data were collected using questionnaires and interviews. The data were analyzed qualitatively and quantitatively. The results of needs analysis showed that students need to learn about (1) writing process, (2) students need to know and learn more about types of text, (3) students need to learn more about types of letter and (4) students need to learn about the cultures around them. The findings revealed that the English writing instructional materials in terms of aims and approaches, design and organization, language contents, skills, topics, methodology and practical consideration were appropriate for second-year students of English Department.